Study on modification and performance of desulfurizer produced by natural soda ash - Yi, Lu; Wanda, Hu; Bateer, Wu; Tuanyuan, Li; Zhenxing, Liu; Yongpeng, Ma; Hongzhong, Zhang (Chemical papers, 2024)
China’s extensive natural soda ash (NSA) reserves and cost-effective production make it a key material in various chemical industries. This study introduces two innovative modification techniques—physical blending and surface coating with sodium silicate solution (SSS)—to enhance the hygroscopic resistance and dispersibility of NSA desulfurizers. Experimental results indicate that both methods significantly reduce moisture-induced agglomeration, with the 10 wt% SSS-modified NSA achieving optimal desulfurization performance. This improvement is attributed to the formation of a protective silicate film, which enhances flowability and moisture resistance, making it highly suitable for industrial applications in flue gas desulfurization.